Military Neutrality as a Principle of Strategic Orientations of the Republic of Serbia – Problem Solving Approach - Mirković, Vladan M; Stajić, Ljubomir; Radivojević, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
A dynamic and intense social processes and relationships that are a characteristic of the modern world may lead to a large number of sources, forms and carriers of threats that are endangering the safety of an individual, society, state and international community. In such a security environment every state must act in a responsible manner and formulate a national security strategy that will be the basis for the functioning of the security system. The correct strategy decisions should take the reality as it is into account and not what we want to see. This includes consideration of the real nature of international relations, the relations between the great powers and their interests, then the regional security factors and their role in achieving the interests of the great powers. The military neutrality of the Republic of Serbia is an expression of a desire to make an important step towards reconciliation and cooperation in the region after decades of conflict and suffering. However, the currently valid paradigm in world politics and security in which the world is observed through the prism of morality and respect for human rights entails being in alignment with one side or the other. In such circumstances, neutrality, apart from the possibility of being unsustainable may also be harmful in some cases, all the more so if the interests of the great powers are achieved through regional factors and actors whose interests are opposite to the interests of the Republic of Serbia.